Hatching order affects offspring growth, survival and adult dominance in the joint‐laying Pukeko Porphyrio melanotus melanotus. (15th April 2014) - Dey, Cody J.; O'connor, Constance; Quinn, James S.; Roskaft, Eivin
<x xml:space="preserve">Abstract</x> In birds with asynchronous hatching, hatching order is an important factor in determining offspring phenotype. Many previous studies have demonstrated that later‐hatched offspring show reduced growth and survival during development. However, few studies have followed individuals from hatching to adulthood to test whether the effects of hatching order persist into later life. Here, we explore patterns of hatching order and fitness‐related traits in the Pukeko Porphyrio melanotus melanotus, a cooperatively breeding bird that lives in stable social groups that form linear dominance hierarchies. Pukeko groups sometimes contain two breeding females that lay eggs in the same nest (joint‐laying). Thus, competition between nest‐mates can influence the relative fitness of each laying female. We show that in both single‐clutch and joint‐clutch nests, earlier‐hatched Pukeko chicks grow faster and survive better than later‐hatched brood‐mates. Moreover, earlier‐hatched chicks achieve higher dominance ranks as adults, making this study one of the first to find a relationship between hatching order and adult dominance in wild birds. Finally, we show that in groups with two breeding females, the chicks of the primary female hatch earlier than the chicks of the secondary female. As a result, the offspring of the primary female may be at a competitive advantage, which could have important implications for social dynamics in this species.